Islamic Banking : Issues in Prudential Regulations and Supervision - Errico, Luca.; Farahbaksh, Mitra (Washington, D.C. : International Monetary Fund, 1998)
This paper analyzes the implications of Islamic precepts on banks' structure and activities, focusing on banking supervision issues. It points out and discusses these issues in the context of a paradigm version of Islamic banking, as well as in frameworks that fall between the paradigm version and conventional banking. The case of Islamic banks operating in a conventional system is also examined.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet